Marine coastal ecosystem and ecotoxicology - Gu, Ji-Dong (Ecotoxicology (London, England), 2020)
Environmental pollution from industrialization, urbanization and agriculture is a serious issue facing all countries during economic development. The Pearl River Delta in Southern China offers a unique case for study and documentation on the ecosystem changes during the fast economic development and urbanization over the past 40 years. This collection of papers from a conference on marine coastal pollution and ecotoxicology held in Guangzhou of China provide the current status on the environmental and ecological processes from the intensive urbanization and development. The research information available from this special issue can be used for both a comparison over time and with other locations and countries, and, in addition, for policy making to serve the long-term sustainable development of the region and the world